Deus X [large type] - Jones, Stephen Mack (An August Snow novel, 2024)
"Detroit ex-cop August Snow puts his life on the line to protect a friend from modern-day Templars sworn to protect the name of the Catholic church at all costs. Father Michael Grabowski, a Franciscan priest who has tended the spiritual needs of Detroit's Mexicantown for forty years, has suddenly retired. August Snow, who has known the priest his whole life, finds the circumstances troubling--especially in light of the recent suspicious suicide of another local priest. What dark history is Father Grabowski hiding? The situation takes a turn for the deadly with the appearance at the Detroit diocese of a mysterious priest and combat vet calling himself Francis Dominioni Petra. The man comes from the Vatican, and as his armored guard circles closer and closer to Father Grabowski and his friends, August wants to know why. A terrible crime has been committed in the name of faith--but who is seeking justice, and who is trying to bury the truth and any of its witnesses?"--